Empowering website based information and service quality: the role of backend developer in village digitalization - Daffa Ahmadhan Khusumah; Agus Virgono; Faisal Candrasyah Hasibuan (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2023)
In today's technology-driven era, this paper investigates the indispensable role of backend developers in empowering website-based information and service quality through digitization initiatives. As technology is critical in service delivery and information dissemination, backend developers are crucial in developing robust and efficient systems. This paper emphasizes the importance of their position by examining their primary responsibilities, skills required, challenges faced, and their impact on improving the quality of website-based services and information in the digitization process. By studying the realm of backend development, this paper highlights the vital contribution made by backend developers in achieving effective digital transformation.